(3GdQMdI GdJjLGfjIs - (3YHO Gddg GdJjLGfj,J (B708 (3g` s ((3MSjf Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi hgPG JbjjO jTJed Ydi hUa s
(3BNQgG (B:s
(3hgh GdSejY dfG hCfJ s
(3HgG fXGe GdJYbjHIs
(3JcQQJ CjVkG JMJ Qbe (B" 27" (3GdLZQGajG hGdHdOGfs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B39s
Keywords: (3GdLZQGajG h GdHdOGfs